The church of women : gendered encounters between Maasai and missionaries - Hodgson, Dorothy Louise (Indiana University Press, 2005)
In Africa, why have so many more women converted to Christianity than men? What explains the appeal of Christianity to women? What does religious conversion mean for the negotiation of gender and ethnic identity? What role does religious conversion play as a tool for empowering women? In The Church of Women, Dorothy L. Hodgson looks at how gender has shaped the encounter between missionary priests and Maasai men and women in Tanzania. Building on her extensive experience with Maasai and the Spiritan missi.